Warhol after Warhol : power and money in the modern art world - Dorment, Richard (Picador, 2023)
"Late one afternoon in the winter of 2003 art critic Richard Dorment answered a telephone call from a stranger. The caller was Joe Simon, an American film producer and art collector. He was ringing at the suggestion of David Hockney, his neighbour in Malibu. A committee of experts called the Andy Warhol Art Authentication Board had declared the two Warhols in his collection to be fake. He wanted to know why and thought Dorment could help. This call would mark the beginning of an extraordinary story that would play out over the next ten years and would involve a cast of characters straight out of fiction. From rock icons and film stars; art dealers and art forgers; to a murdered Russian oligarch and a lawyer for the mob; from courtrooms to auction houses: all took part in a bitter struggle to prove the authenticity of a series of paintings by the most famous American artist of the 20th century. Part detective story, part art history, part memoir, part courtroom drama, Warhol After Warhol is a spellbinding account of the dark connection between money, power and art"--Publisher's description